IMPLEMENTASI PEMBELAJARAN BIOLOGI BERBASIS SCIENTIFIC APPROACH DI SMA SWASTA UISU MEDAN TAHUN PEMBELAJARAN 2016/2017 - Gepi Dianisa Dalimunthe; Amrizal Amrizal; Sespin Renova; Nina Ratna Siregar (Jurnal Pelita Pendidikan, 2017)
This research aimed to know: (1) suitability  of plan of  learning was made by biology teacher with plan of  learning based of curicullum 2013; (2) suitability of the implementing of  biology learning based on scientific approach with the implementation plan of  learning; (3) implementing of learning experience of scientific approach in biology learning; (4) experience learning of scientific approach that is relatively difficult on the implementing of  scientific approach in biology learning; (5) Solution in solving obstacles of implementing learning experience of scientific approach in biology learning .Type of this research was  quantitative descriptive research. The population of this research was the biology teacher of class X and XI which amounted to 2 people and 111 students of class X and XI. Total sample were 2 teachers and 98 students. The research data was taken by observation, questionnaire, interview and documentation.The results showed that: (1) the suitability  of plan of  learning was made by biology teacher with plan of  learning of curicullum 2013 belonging to the category was good (87,63%); (2) the  suitability of the implementing of  biology learning biology learning based on scientific approach with the implementation plan of  learning belonging to the category was quite (74.51%); (3) the implementing of learning experience of scientific approach in biology learning by student overall  was less (48%) With the dominant learning experience was observed (81%) with forms of learning experience in the form of reading, listening, listening and seeing; (4) The learning experience of scientific approach not dominant was associate belonging to the category was less (7%); (5)  Solution to overcome obstacles are provides practice to students to solve problems and states the argument, use media in learning gives reward and provide the learning references to students; doing peer discussionsKeywords:  learning, learning experience, scientific approach.